PERCEPTION OF COVID-19 AND REPRODUCTIVE HEALTH OF FEMALE AND MALE ADOLESCENTS IN URBAN AREAS IN THE SUSTAINABLE DEVELOPMENT GOALS - Pristya, Terry Y. R.; Herbawani, Chahya Kharin; Karima, Ulya Qoulan; Oktafiyanti, Arnur; Ramadhanty, Nadia; Ginawang, Asto (UI Scholars Hub, 2022)
Sustainable Development Goals (SDGs) in goal 3 (good health and well-being) and goal 4 (equality in education) for all specifically targeted at vulnerable groups. Adolescents were a part of it. A decade of progress in reproductive health could be stalled by covid-19. The study aimed to analyze reproductive health and adolescents’ perceptions during the covid-19 pandemic era in urban areas. This descriptive study used an online survey conducted in Jakarta. The sample consisted of 438 adolescents selected by convenience sampling technique. The results were that both female and male adolescents had poor knowledge about HIV/AIDS transmission (female = 77.0%; male = 74.7%) and pregnancy even if only by one sexual intercourse (female = 93.4%; male = 81.4%). The webinars and online counseling in total have more than 75% of respondents who rarely and never been given from educational institutions. There was a large difference between female adolescents (4.5%) and males (13.4%) in the proportion gap related to the perception that the covid-19 were at no risk of reproductive health problems. Conclusion. it was necessary to optimize the role of educational institutions on reproductive health knowledge through webinars and online counseling.